2007
DOI: 10.1021/nl070058c
|View full text |Cite
|
Sign up to set email alerts
|

Dipole−Dipole Interactions in Nanoparticle Superlattices

Abstract: Nanoparticles often self-assemble into hexagonal-close-packed (hcp) structures although it is predicted to be less stable than face-centered-cubic (fcc) packing in hard-sphere models. In addition to close-packed fcc and hcp superlattices, we observe formation of nonclose-packed simple-hexagonal (sh) superlattices of nearly spherical PbS, PbSe, and gamma-Fe2O3 nanocrystals. This surprisingly rich phase diagram of monodisperse semiconducting nanoparticles is explained by considering the interactions between nonl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
353
3

Year Published

2008
2008
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 317 publications
(367 citation statements)
references
References 41 publications
11
353
3
Order By: Relevance
“…The discovered self-assembly phenomena are of high relevance for fundamentally science and for (bio-) medical applications involving control of superparamagnetic nanoparticles assembly in the presence of strong external magnetic fields (19). It underlines the importance of dipolar interactions in nanoparticle assemblies (7), and opens a previously unidentified pathway to controlled nanoparticle assembly in solution (20,21).…”
Section: Significancementioning
confidence: 85%
See 1 more Smart Citation
“…The discovered self-assembly phenomena are of high relevance for fundamentally science and for (bio-) medical applications involving control of superparamagnetic nanoparticles assembly in the presence of strong external magnetic fields (19). It underlines the importance of dipolar interactions in nanoparticle assemblies (7), and opens a previously unidentified pathway to controlled nanoparticle assembly in solution (20,21).…”
Section: Significancementioning
confidence: 85%
“…Only recently, it was reported that cube-shaped magnetic nanoparticles of 13 nm showed a surprising magnetic-field-induced assembly into helices at the air-liquid interface (4) and 9-nm magnetic nanoparticles in the presence of a magnetic field uniquely assembled into very large, nearly defectfree monolayers and 3D cubic assemblies on solid substrates (5). This triggers the question about the arrangement of the magnetic dipoles in such assemblies where an amazing answer was recently found in the case of only eight dipoles (6), and where for larger magnetic nanoparticles and their assemblies considerable complexity was observed (7,8).…”
mentioning
confidence: 99%
“…A similar assessment of the role of dipolar interactions has been made by Talapin et al, which considered inorganic nanoparticles with an extremely large dipole moment of 100 D (which is an order of magnitude larger than any organic molecule) and a radius of 5.8 nm. 39 Even in such an extreme case, the dipolar energy was only −39 meV/particle, which is still significantly less than a hydrogen bond energy. This analysis suggests that the dipole energy is unlikely the governing factor in organic self-assembly.…”
Section: B Analysis Of the Dipole-dipole Interactionmentioning
confidence: 98%
“…The observed spread of the excess charge could be important for models of nanoparticle self-assembly that usually treat nanocrystals as point dipoles or assume that excess charge is perfectly localized on the polar surfaces [7,9] These assumptions would lead to quantitatively, or even qualitatively, incorrect results at short distances. Furthermore, the delocalization of charge suggests that nanorods may be highly polarizable, which could significantly affect the interactions between nanorods.…”
mentioning
confidence: 99%